PELACAKAN KONTAK TUBERKULOSIS SECARA SENTRIFUGAL TERHADAP ANAK KONTAK ERAT DENGAN PENDERITA TUBERKULOSIS PARU DEWASA: FAKTOR KEDEKATAN DAN RISIKO INFEKSI - , DIANA BANCIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Children who are in close contact with an adult having pulmonary tuberculosis (TB) are at increased risk to get the infection. The risk of infection increases with closeness and duration of contact. Limited studies reported the relationship of degree of closeness and the risk of TB infection. Objective: To evaluate closeness of contact as a risk factor of TB infection among children close contact with adult having pulmonary TB. Methods: Case-control study conducted in children aged â¤ 15 years in close contact with smear positive pulmonary tuberculosis patients during August 2009 - June 2012. The primary outcome was the risk factor of closeness to TB infection. Different proportions between the two groups were analyzed with Chi square (X2), followed by multivariate analysis using logistic multiple regression. Results: Total of 198 children study subjects, consisting of 100 children infected with tuberculosis and 98 children who are not infected. In univariate analysis the index female, sputum smear AFB +3, sleeping in same room, and sleeping in same bed was statistically significant as a risk factor for TB infection with OR of 1,77 ( CI 95% 1,00-3,11), 3,08 (CI 95% 1,70-5,58), 2,06 (CI 95% 1,15-3,66), 2,49 (CI 95% 1,32-4,70), respectively. In multivariate analysis, sputum smear AFB +3, sleeping in same bed and nursing was statistically significant as a risk factor for TB infection with OR of 4,08 (CI 95% 2,13-7,8), 3,08 (CI 95% 1,53-6,20), 1,99 (CI 95% 1,02-3,87), respectively. Conclusions: Case index with sputum smear AFB +3, sleeping in same bed with an index case of TB and nursing is a risk factor in children who are close contacts. Mothers or parents as index case, index female, duration of contact > 9 hours/day, sleeping in same room, the intimacy of activity including breastfeeding, feeding, and eating together 3x/day are not associated with TB infection.